2020
DOI: 10.1007/s42977-020-00016-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential epidemiology and antibiotic resistance of lactose-fermenting and non-fermenting Escherichia coli: Is it just a matter of taste?

Abstract: Urinary tract infections (UTIs) are some of the most common infections affecting humans worldwide. Occurrence of atypical, lactose non-fermenting, biochemically "inactive" strains of E. coli in clinical material has been described in the literature, which may cause a significant diagnostic challenge. The present retrospective microbiological study was carried out using isolates and data collected between January 1, 2013, and December 31, 2017, at the Institute of Clinical Microbiology. n = 24,285 positive urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Nevertheless, in another study by Gajdács et al, the antibiotic susceptibilities of lactose-fermenting and non-fermenting E. coli from UTIs were compared during a 5-year study period in Southern Hungary. In this study, it was found that the resistance rates of lactose non-fermenters were higher for fluoroquinolones, fosfomycin and nitrofurantoin in both inpatients and outpatients [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in another study by Gajdács et al, the antibiotic susceptibilities of lactose-fermenting and non-fermenting E. coli from UTIs were compared during a 5-year study period in Southern Hungary. In this study, it was found that the resistance rates of lactose non-fermenters were higher for fluoroquinolones, fosfomycin and nitrofurantoin in both inpatients and outpatients [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The morning midstream urine and urine from the urinary catheter were collected from patients under complete aseptic conditions and cultured on blood and MacConkey agars (Oxoid Ltd., England) to detect different E. coli strains. 15 The isolated UPEC was confirmed by Gram staining and the standard biochemical tests and only one isolate from each patient was investigated. 16 The UTI was confirmed by isolation of >10 5 colony-forming units (CFU) UPEC/mL midstream urine and ≥10 3 CFU UPEC/mL catheterized urine.…”
Section: Methodsmentioning
confidence: 99%
“…The MICs of colistin were determined by the broth microdilution in cation-adjusted Mueller-Hinton Broth (CAMHB). 23 The MIC breakpoint of colistin for E. coli was interpreted following the European Committee on Antimicrobial Susceptibility Testing (EUCAST 2019) 24 (susceptible, ≤2 mg/L; resistant, >2 mg/L). The E. coli ATCC 25,922 served as the quality control for susceptibility testing.…”
Section: Bacterial Strainsmentioning
confidence: 99%